2015
DOI: 10.1021/acs.organomet.5b00267
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Rationalizing the Conditions for the Isomerization of 1,5-Cyclooctadiene in Iridium Complexes by Experimental and Theoretical Mechanistic Studies

Abstract: The independent synthesis of the biscarbene complexes [Ir(cod)(vegi R )]PF 6 (2) (cod =1,5-cyclooctadiene, vegi R = bidentate N-heterocyclic carbene) as well as their isomerized complexes [Ir(1-κ-4,5,6-η-C 8 H 12 )(NCCH 3 )(vegi R )]-PF 6 (3) is described. We elucidated acetic acid as the catalyst and coordinated acetonitrile as the thermodynamic driving force for this cod-isomerization. By using the stronger trifluoroacetic acid, we isolated complex [Ir(cod)(F 3 CCO 2 )(H)(vegi nPr )]PF 6 (7a) as an intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…The carbene–Li distances of 2.22–2.23 Å match those of complex E but are longer than those typically reported for NHC-Li complexes (2.09–2.20 Å) . The bite angle C1–Li–C8 is 80.1°, which is a value also found for vegi R complexes of transition-metal complexes. ,, The C1–C8 carbene distance of 2.89 Å is only slightly shorter than the value for the imidazolium salt 1b (3.04 Å) and the calculated value (DFT) for the free carbene 5b (2.98 Å) (see the Supporting Information). It lies right within the broad range of 2.67–3.26 Å observed for this ligand system so far .…”
Section: Resultssupporting
confidence: 66%
“…The carbene–Li distances of 2.22–2.23 Å match those of complex E but are longer than those typically reported for NHC-Li complexes (2.09–2.20 Å) . The bite angle C1–Li–C8 is 80.1°, which is a value also found for vegi R complexes of transition-metal complexes. ,, The C1–C8 carbene distance of 2.89 Å is only slightly shorter than the value for the imidazolium salt 1b (3.04 Å) and the calculated value (DFT) for the free carbene 5b (2.98 Å) (see the Supporting Information). It lies right within the broad range of 2.67–3.26 Å observed for this ligand system so far .…”
Section: Resultssupporting
confidence: 66%
“…223 Further mechanistic studies on this carboxylate-induced COD isomerisation were performed by Kunz on the related [Ir(C^C)(COD)] + system, 175, where C^C is a chelating bis-NHC ligand (see Figure 75). 225 Experimental studies showed that formation of the isomerised product [Rh(C^C)I2(OAc)] complexes (where C^C = bidentate 'normal' and 'abnormal' NHCs linked by a -(CH2)3-unit) exhibit C(sp 3 )-H activation of the linker's central CH2 group. This process occurs more readily with the abnormal NHCs, and BP86(MeCN) calculations suggest these induce an easier predissociation of iodide, rather than having any direct effect on the AMLA/CMD C-H activation step.…”
Section: Intramolecular C(sp 3 )-H Bond Activationmentioning
confidence: 99%
“…This surprisingly low selectivity combined with the facile isomerization/racemization of 3b upon treatment of 10 with HCl (vide infra) was suggestive of a rhodium-mediated isomerization of the ligand also during catalysis. 23…”
Section: Results and Discussionmentioning
confidence: 99%